2009
DOI: 10.1093/sw/54.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Risk and Resilience-Based Out-of-School Time Program for Children and Youths

Abstract: Out-of-school time (OST) programs offer a unique opportunity to provide educational supports to high-risk children and youths.The authors describe the utility of applying principles of risk and resilience to the development and evaluation of an OST program. Academic outcomes among participants at the Bridge Project, an OST program located in three urban public housing communities, are presented to illustrate a risk and resilience approach to service delivery. Implications for practice and research are delineat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 7 publications
0
20
0
4
Order By: Relevance
“…Rutter (28) refiere que los recursos son contextuales y varían de un individuo a otro; sin embargo, dependiendo de la situación de riesgo los recursos utilizados en cada individuo son diferentes de acuerdo con la circunstancia (29,30). Algunos investigadores refieren que la persona, al identificar el riesgo, utiliza los factores de protección internos para llegar a la recuperación (5,31,32). Estos factores permiten amortiguar las consecuencias de los peligros e interrumpen la cadena causa y efecto bloqueando los resultados negativos.…”
Section: Protección Individual Contra El Riesgo Sexualunclassified
See 1 more Smart Citation
“…Rutter (28) refiere que los recursos son contextuales y varían de un individuo a otro; sin embargo, dependiendo de la situación de riesgo los recursos utilizados en cada individuo son diferentes de acuerdo con la circunstancia (29,30). Algunos investigadores refieren que la persona, al identificar el riesgo, utiliza los factores de protección internos para llegar a la recuperación (5,31,32). Estos factores permiten amortiguar las consecuencias de los peligros e interrumpen la cadena causa y efecto bloqueando los resultados negativos.…”
Section: Protección Individual Contra El Riesgo Sexualunclassified
“…En este sentido, la resiliencia basada en prevención se dirige a fortalecer los factores protectores que posee el individuo y a disminuir los factores de riesgo (4) permitiendo de esta forma dar solución a problemas de salud que afectan de manera importante a los adolescentes. La resiliencia ha mostrado su efectividad en diversas intervenciones ya que promueve el proceso de superar los efectos negativos de la exposición al riesgo, el afrontamiento exitoso de las experiencias estresantes, y la evitación de las trayectorias negativas asociadas al riesgo (5,6,7). La Organización de las Naciones Unidas para la Educación, la Ciencia y la Cultura (8) estima que en el 2030 existirán más de 40 millones de adolescentes que se infectarán con el VIH en todo el mundo.…”
Section: Introductionunclassified
“…The Bridge Project has been providing services to low-income youth in housing developments for 17 years; the project's connection with the University of Denver allows significant opportunity for research and evaluation. Evaluation protocols aimed at assessing the needs of participants and the effects of the program are a critical aspect of the Bridge Project (Anthony et al 2009). …”
Section: Overviewmentioning
confidence: 99%
“…The mission of the Bridge Project is to help children and youth living in public housing neighborhoods achieve their academic potential and graduate with the resources necessary to succeed as adults (Anthony et al 2009). Intervention elements include tutoring, mentoring, and academic, personal and social skill-building groups.…”
Section: Intervention Strategiesmentioning
confidence: 99%
“…There are a plethora of community-based youth development programs throughout the United States, and attending these community-based programs has been found to be associated with lower levels of child problem behavior (i.e., substance use and delinquency), improved academic performance, increased school attendance and commitment, more positive peer relations, a more positive self-concept, lower perceptions of community disorganization, and increased prosocial behavior (e.g., Anderson-Butcher, 2000;Anderson-Butcher & Cash, 2010;Anthony, Alter, & Jenson, 2009;Fleming et al, 2008;Huang, Gibbons, Kim, Lee, & Baker, 2000;Mahoney & Cairns, 1997;Peck, Roeser, Zarrett, & Eccles, 2008;Schinke et al, 2000;Schinke, Orlandi, & Cole, 1992;Shernoff, 2010). For example, Anderson-Butcher et al (2003) found that simply attending a Boys and Girls Club was associated with increased academic achievement and lower levels of truancy.…”
Section: Youth Program Attendancementioning
confidence: 99%